COOPERATION WITH FOREIGN COUNTRIES IN THE DEVELOPMENT OF GREEN ECONOMY IN UZBEKISTAN - Mardanova Rano Isakovna (Scholar Express Journals, 2025)
The article discusses the importance of international cooperation for the implementation and development of a green economy in Uzbekistan. It emphasizes the role of international partners and organizations in ensuring sustainable development through the introduction of environmentally friendly technologies, the development of renewable energy sources, efficient water management, increased energy efficiency and the modernization of urban infrastructure. Specific examples of cooperation with countries such as Germany, China, Turkey, India, Japan, Israel and others, as well as with international organizations, including the World Bank and UNDP, are analyzed. A conclusion is made about the strategic importance of a green economy for improving the quality of life of the population and preserving natural resources
Keywords: green economy; sustainable development; international cooperation